Auditoría informática de la seguridad física y lógica de las computadoras del Centro de Educación Continua de la Utmach. - Guaman Poma (My University, 2019)
The audit in the computer systems is an intrinsic science in every organization, it allows to analyze all the relevant aspects related to automation, solve services, security, protection, management and governance of both tangible and intangible resources. The Universidad Técnica de Machala, being an entity of higher education, must maneuver immense amounts of data, make a series of processes, tasks, services and implements flow in a holistic manner to exercise its daily functions within society; its structure composed of academic units, departments, authorities, councils, units such as the student welfare center and continuing education center (C.E.C) that is responsible for organizing courses, language institute, training, advertising, strategic agreements, among other motions to maintain the current knowledge of all those involved in their corporate environment. This case study includes the description and explanation of all the measures that the C.E.C abides to maintain levels of security / acceptable protection in their computers, being approached from an abductive perspective of an exploratory and pragmatic nature in order to propose improvements and favorable inferences to the performance of the area analyzed.
La auditoría en los sistemas informáticos es una ciencia intrínseca en toda organización, permite analizar todos los aspectos relevantes referentes a automatización, solventar servicios, seguridad, protección, gestión y gobierno tanto de recursos tangibles como intangibles. La Universidad Técnica de Machala al ser una entidad de educación superior, debe maniobrar inmensas cantidades de datos, hacer fluir en forma holística una serie de procesos, tareas, servicios e implementos para ejercer sus funciones cotidianas dentro de la sociedad; su estructura compuesta por unidades académicas, departamentos, autoridades, consejos, unidades como la de bienestar estudiantil y centro de educación continua (C.E.C) que se encarga de organizar cursos, instituto de idiomas, capacitaciones, publicidad, convenios estratégicos, entre otras mociones para mantener la actualidad en conocimientos de todos los involucrados en su ámbito corporativo. Este caso de estudio comprende la descripción y explicación de todas las medidas que acata el C.E.C para mantener niveles de seguridad/protección aceptable en sus ordenadores, siendo abordada desde una perspectiva abductiva de carácter exploratorio y pragmático, a fin de proponer mejoras e inferencias favorables al desempeño del área analizada.
Keywords: AUDITORÍA INFORMÁTICA; CONTROLES; CENTRO DE CÓMPUTO; EDUCACIÓN